ANDROID-BASED MOBILE LEARNING APPLICATION AS A LEARNING EXERCISE FOR STUDENTS - Ayu Faradillah; Diar Fadilah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2020)
This study aimed to develop a mobile learning application as a learning exercise for students in Mathematics learning. The research method used was the Research and Development (R&D) with a Four-D (4D) development model. This study utilized a questionnaire to analyze students’ needs for mobile learning applications in Mathematics learning, which was filled out by 101 students. The analysis was performed using the Rasch Model. The results of the analysis show that students need applications to help the learning process such as collecting assignments that can be done anywhere and at any time as well as features equipped with mathematical symbols to smooth the discussion with teachers and classmates. Therefore, the design of the mobile learning application developed has a database that is divided into 2 local hosts, including those for teachers and students. The database can connect teachers and students, and students can complete assignments anytime and anywhere, and write mathematical symbols. Based on the results of the study, the Cadudasa mobile learning application received a feasibility assessment by media experts with a percentage of 84% in the good category. Student responses to the Cadudasa mobile learning application were 86% in the very good categories. The results of this study indicate that the Cadudasa mobile learning application is considered appropriate to being used as a medium of learning in schools Penelitian ini memiliki tujuan untuk mengembangkan aplikasi mobile learning sebagai learning exercise bagi siswa dalam pembelajaran matematika. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model pengembangan Four-D (4D). Penelitian ini menggunakan angket analisis kebutuhan siswa terhadap aplikasi mobile learning dalam pembelajaran matematika dimana total siswa yang mengisi angket sebanyak 101 orang. Analisis dilakukan dengan menggunakan Rasch Model. Berdasarkan hasil analisis diperoleh bahwa siswa membutuhkan aplikasi yang dapat membantu proses pembelajaran seperti pengumpulan tugas yang dapat dilakukan dimanapun dan kapanpun serta adanya fitur simbol-simbol matematika yang memudahkan untuk berdiskusi dengan guru dan teman sekelasnya. Sehingga, desain aplikasi mobile learning yang dikembangkan memiliki database yang dibagi menjadi 2 localhost yaitu untuk guru dan siswa, database tersebut dapat terkoneksi anatara guru dan siswa, kemudian siswa dapat menyelesaikan tugas dengan waktu kapanpun dan dimanapun, dan dapat menuliskan simbol-simbol matematika. Berdasarkan hasil penelitian, aplikasi mobile learning Cadudasa mendapatkan penilaian kelayakan oleh ahli media dengan persentase 84% dengan kategori baik. Respon siswa terhadap aplikasi mobile learning Cadudasa mendapatkan hasil 86% dengan kategori sangat baik. Hasil penelitian ini menunjukan bahwa aplikasi mobile learning Cadudasa dinyatakan layak untuk dijadikan sebagai media pembelajaran di sekolah.